PENGARUH HARGA KARET TERHADAP KESEJAHTERAAN PETANI KARET DI KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Randi Meifrima; Henny Indrawati; Caska ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aim to to know influence of Rubber price to prosperity of Farmer Of Rubber In Kecamatan Kuantan Hilir Kabupaten Kuantan Singingi. This Research is conducted inKecamatan Kuantan Hilir Kabupaten Kuantan Singingi. Research done by since proffering of title in September up to research time finish. As for this research type is quantitative descriptive research, that is explaining result of research which in the form of datas of kuesioner which later; then in test and analysed constructively peripheral of SPSS. As for used data collecting technique that is with study method of survey. Pursuant to result of test of t known that price have an effect on signifikan to prosperity of farmer of rubber in Kecamatan Kuantan Hilir Kabupaten Kuantan Singingi. This Matter pursuant to result of test t indicating that price variable (X) with value of t calculate 4.599 > t ofis tables of 1,975 with value of Sig equal to 0.000 < 0.05 meaning H0 refused and H1 accepted. While pursuant to result of coefficient test of determinasi (R2) known that value of R Square in this research equal to 0.611, laterthen assess this will be altered to percent. This of its meaning of percentage of contribution influence of price variable (X) to prosperity of farmer of rubber inKecamatan Kuantan Hilir Kabupaten Kuantan Singingi is equal to 61,1 %, while the rest 38.9 % influenced by other variable which do not check in this research.Keywords: Price, Prosperity.